1999
DOI: 10.1055/s-2007-978805
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Orexin A on Thyrotropin-Releasing Hormone and Thyrotropin Secretion in Rats

Abstract: Effects of orexin A on secretion of thyrotropin-releasing hormone (TRH) and thyrotropin (TSH) in rats were studied. Orexin A (50 microg/kg) was injected iv, and the rats were serially decapitated. The effects of orexin A on TRH release from the rat hypothalamus in vitro and on TSH release from the anterior pituitary in vitro were also investigated. TRH and thyroid hormone were measured by individual radioimmunoassays. TSH was determined by the enzyme-immunoassay method. The hypothalamic TRH contents increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 4 publications
0
34
2
Order By: Relevance
“…This wide distribution of OX fibres and OX receptors indicates that OXs may play an important role in physiological functions other than feeding. Recent data show that OXs stimulate the expression of c-Fos in the paraventricular and arcuate nucleus, and peripheral administration of OX inhibited plasma thyrotrophin levels as well as in vitro hypothalamic thyrotrophin-releasing hormone release (12). Furthermore, OX-A and OX-B have been reported to modulate in vivo luteinizing hormone secretion (13,14), the hypothalamic -pituitary-adrenal axis (15) and in vitro GH secretion from porcine somatotrophs.…”
Section: Introductionmentioning
confidence: 99%
“…This wide distribution of OX fibres and OX receptors indicates that OXs may play an important role in physiological functions other than feeding. Recent data show that OXs stimulate the expression of c-Fos in the paraventricular and arcuate nucleus, and peripheral administration of OX inhibited plasma thyrotrophin levels as well as in vitro hypothalamic thyrotrophin-releasing hormone release (12). Furthermore, OX-A and OX-B have been reported to modulate in vivo luteinizing hormone secretion (13,14), the hypothalamic -pituitary-adrenal axis (15) and in vitro GH secretion from porcine somatotrophs.…”
Section: Introductionmentioning
confidence: 99%
“…DIA animals present a higher synthesis of Ox-R1 than that of FFR, which may be interpreted as a compensatory increase due to poor peptide release in those animals, and also as an impaired receptor signaling; it has been observed in other models of anorexia (Ballinger et al, 2001). It is likely that orexins released in the PVN or food-restricted rats inhibit TRH release, and in consequence, TSH serum levels also are low, as has been observed by an icv injection of orexins (Mitsuma et al, 1999). Using the DIA paradigm it is evident that anorexic animals do not have that pathway activated thus, the differential change in Ox-R1 mRNA levels between FFR and DIA groups could be an additional responsible factor for the enhanced expression of proTRH in the PVN of dehydrated rats.…”
Section: Tshmentioning
confidence: 72%
“…The longer effects of OxA probably are attributable to the molecular structure, thanks to which it is more resistant than OxB to an attack of inactivating peptidases [41].The experiments also displayed functions of orexins -other than the metabolic one. It was confirmed that orexins play a modulating role in the regulation of the hypothalamicpituitary-thyroid axis [45], -adrenal axis [46] and -gonadal axis [47].…”
Section: The Role Of Orexins and Leptin In The Regulation Of The Secrmentioning
confidence: 83%